Assessment of knowledge, attitude and practices of risk factors of oral cancer among the adult population of rural field practice area of Bangalore Medical College and Research Institute - Crastha, Sofiya; Thangaraj, Selvi; Sobagiah, Ranganath Thimmanahalli (International Journal Of Community Medicine And Public Health, 2018)
Background: Cancer is the non-communicable disease of public health importance. The oro-pharyngeal cancer is more common in developing than in developed countries. In India, oral cavity cancer is among the top five most common cancers in both sexes. Oral cancer is multi-factorial in nature, most of these risk factors can be prevented.The survival rate in oral cancer is directly related to the stage of diagnosis. Early diagnosis increases the probability of cure and minimizes the deformity. This study intends to find out the knowledge, awareness and practice of risk factors of oral cancer among rural population and to provide them health education about the prevention and early diagnosis. Methods: The cross sectional descriptive study was conducted in the rural field practice area of BMCRI (Bangalore Medical College and Research Institute), among 311 adults. Results: Majority, 195 (62.8%) of the population did not know the site of oral cancer, 248 (79.8%) did not know any clinical features of the oral cancer and 117 (37.6%) did not know about any risk factors of oral cancer. About 177 (56.90%) people agreed that there is a need for screening and regular oral examination to detect the lesions early. Only 42 (13.5%) had undergone oral examination done in the last 1 year. Conclusions: There is a need to generate awareness regarding the risk factors and about the good and harmful practices in the community.